LOCALIZATION AND HISTOLOGICAL STRUCTURE OF SPINAL CORD TUMORS IN PATIENTS IN SUMY REGION - O. O. Potapov; O. P. Kmyta; O. O. Tsyndrenko; N. O. Dmytrenko; E. V. Kolomiets; V. V. Pokhmura; M. P. Khavro; T. V. Bereznyi (Eastern Ukrainian Medical Journal, 2019)
Spinal cord tumors include tumors developing from its parenchyma, vessels, roots and membranes. The main theory of the formation of spinal cord tumors is the polyetiological dysontogenetic theory. According to this theory, hereditary factors, dysembriogenesis, trauma, carcinogenic effects, viral infection, intoxication, radiation, etc. play an important role in the development of tumors. Although scientists keep finding out more about genetic and environmental factors influencing the development of many types of tumors, spinal tumors are still a relatively unknown subject. Spinal tumors partially contain pathological genes, but in many cases, researchers don't know what causes these genetic changes. Tumors of the central nervous system (CNS) make up 12% of all tumors, tumors of the spinal cord – 3% of nervous system disorders, in the structure of malignant lesions of the CNS – 1,4-5%, occur mainly at the age of 20-60 years. In children, as well as in elderly and senile persons, these tumors are rare. Most often, they develop not from the brain matter, but from the surrounding tissue, and when they increase in size, they compress the spinal cord. Spinal tumors are usually divided into primary and secondary. The group of primary tumors include tumors, originating from the brain matter (intramedullar tumors), and those that grow from the membranes of the brain, roots, vessels (extramedullar tumors). Extramedullar tumors are much more common (in 80% of all spinal tumors) than intramedullar tumors. Extramedullar tumors can be both subdural and epidural. The majority of extramedullar tumors are subdural. Occasionally there are tumors, some of which are located inside the dural sac, and some – outside the dura mater, they are subdural-epidural tumors, as well as epidural-extrovertebral tumors. Among extramedullar tumors the most commonly diagnosed are meningiomas and neurinomas, among intramedullar the most common are ependymomas, less common are astrocytomas and oligodendroglioma. Glioblastomas of the spinal cord is extremely rare; the most common metastases from the posterior fossa are medulloblastomas. Intracerebral tumors of the spinal cord are characterized by greater biological benignity, than similar brain tumors. Extracerebral spinal cord tumors have no such differences in their biological properties. In general, spinal cord tumors are more common in elderly patients. Neurinomas and meningiomas predominate in adults, and ependymomas and dysgenetic tumors (teratoma, epidermoid cysts) – in children. Peculiarities of etiopathogenetic aspects, clinical course, influence on socio-economic factors encourage further improvement of diagnosis and more detailed study of this type of tumors. Materials and methods. The analysis of medical records of patients with spinal cord tumors, who were hospitalized in neurological departments of the Sumy Regional and 4th City Clinical Hospitals in 2015-2018 was carried out. 69 clinical cases were processed in order to investigate the prevalence of spinal cord tumors in the Sumy region, the characteristics of the disease in this group of patients, the leading symptoms, methods of diagnosis and treatment. The analysis of statistical data, obtained after processing of the research materials, was carried out using the licensed version of the IBM SPSS Statistics 17 software. Our study significantly established that, according to the histological structure, in 46 patients (28 women and 18 men) meningiomas were predominant and that in 31 patients they were located at the level of Th6-Th12. Mainly in 42 patients (33 women and 9 men, p<0.05) spinal cord neoplasms were localized at the level of Th6-Th12, with extramedular-intradural tumor location – 57 patients (38 women and 19 men). According to our study, pain syndrome significantly prevailed in 42 patients (35 with extramedular-intradural tumor localization). The study of the histological structure of tumors depending on their localization is an integral part of both diagnosis and treatment, and an important component of predicting the quality of life of the patient.